Ossified Chronic Subdural Hematoma with Armored Brain - Kaplan, Metin; Akgun, Bekir; Secer, Halil Ibrahim (Turkish Neurosurgical Soc, 2008)
Ossified chronic subdural hematoma is a very rarely seen entity. We present here a 22-year-old male who had presented with severe headache consequent to brain compression caused by bifronto-parieto-temporal ossified subdural hematoma. We evaluated our method and surgical intervention in the light of the literature. The question whether the ossified membrane should be excised or not excised in these cases is a matter of controversy. We think that an ossified membrane causing an armored brain appearance should be excised in symptomatic, young patients with prominent cerebral compression. During this dissection the relatively thickened arachnoid mater provides a safe border.
Ossifiye kronik subdural hematom ile Zırhlı beyin
Keywords: Armored brain; Ossified chronic subdural hematoma; Surgical treatment; Hematoma